2013
DOI: 10.1371/journal.pone.0071303
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Assessment of an Intervention to Debias Adolescents against Causal Illusions

Abstract: Researchers have warned that causal illusions are at the root of many superstitious beliefs and fuel many people’s faith in pseudoscience, thus generating significant suffering in modern society. Therefore, it is critical that we understand the mechanisms by which these illusions develop and persist. A vast amount of research in psychology has investigated these mechanisms, but little work has been done on the extent to which it is possible to debias individuals against causal illusions. We present an interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 54 publications
(79 reference statements)
1
42
0
1
Order By: Relevance
“…To some extent, optimistic beliefs are sensitive to evidence. It has been shown that some forms of optimism and self-enhancement can be reduced or at least controlled by providing people with more information and making them more accountable for the accuracy of their predictions (e.g., Barberia et al, 2013, Sedikides et al, 2002, Weinstein, 1980). For instance, Sedikides argues that via introspective reflection people can control self-enhancing beliefs at least in the short-term, and that self-assessment is more accurate when people are held accountable for it (Sedikides, Horton, & Gregg, 2007).…”
Section: Are Unrealistically Optimistic Predictions Fixed?mentioning
confidence: 99%
“…To some extent, optimistic beliefs are sensitive to evidence. It has been shown that some forms of optimism and self-enhancement can be reduced or at least controlled by providing people with more information and making them more accountable for the accuracy of their predictions (e.g., Barberia et al, 2013, Sedikides et al, 2002, Weinstein, 1980). For instance, Sedikides argues that via introspective reflection people can control self-enhancing beliefs at least in the short-term, and that self-assessment is more accurate when people are held accountable for it (Sedikides, Horton, & Gregg, 2007).…”
Section: Are Unrealistically Optimistic Predictions Fixed?mentioning
confidence: 99%
“…This assessment procedure is now relatively standard, which facilitates comparisons across experiments and the evaluation of new applied strategies. This methodology has also been used when there is a need to accurately estimate the degree of illusion of causality that people show before and after receiving training on scientific thinking ( Barberia et al, 2013 ), which is of particular interest for the present report.…”
Section: How To Assess the Illusionmentioning
confidence: 99%
“…Following this idea, Barberia et al (2013) told a group of adolescents that they had developed a miracle product that would help them improve their physical and cognitive abilities. This was conducted quite theatrically, and the teenagers were allowed to try the properties of the product (a piece of regular ferrite) through several cognitive and physical exercises.…”
Section: Developing An Educational Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…With this logic in mind, we designed an educational intervention aimed at high school students (Barberia, Blanco, Cubillas, & Matute, 2013). The design of our study comprised three phases that took place in a one-hour session: a staging phase, a workshop phase, and a measurement phase.…”
Section: Preventing Harmful Illusionsmentioning
confidence: 99%